Upregulation of TTYH3 by lncRNA LUCAT1 through interacting with ALYREF facilitates the metastasis in non-small cell lung cancer - Fang Fang; Mei Zhao; Jinming Meng; Jiaqi He; Chunlei Yang; Changhong Wang; Jiaxiao Wang; Sheng Xie; Xiaowei Jin; Wei Shi (Cancer Biology & Therapy)
Metastasis is the predominant culprit of cancer-associated mortality in non-small cell lung cancer (NSCLC). Tweety homolog 3 (TTYH3) reportedly functions vitally in the development of diverse cancers, including NSCLC; nevertheless, its role in NSCLC metastasis remains ambiguous. Quantitative reverse transcription polymerase chain reaction (qRT-PCR) and western blot were initially employed to detect TTYH3 expression in NSCLC and normal lung epithelial cells. Subsequently, A549 and NCI-H1650 cells were chosen as NSCLC models in vitro and transfected with short hairpin RNAs (sh-TTYH3, sh-LUCAT1, and sh-ALYREF) or overexpression plasmids (oe-ALYREF and oe-TTYH3). Transwell assays were used for migrative and invasive tests. Epithelial mesenchymal transformation (EMT)-related proteins (E-cadherin, N-cadherin, Vimentin, and Snail) were measured by western blot. A mouse lung metastasis model was built to define the function of TTYH3 in NSCLC metastasis, followed by hematoxylin-eosin staining. RNA pull-down, RNA immunoprecipitation, qRT-PCR, western blot, and actinomycin D assays were adopted to determine the relationships among LUCAT1, ALYREF, and TTYH3. TTYH3 was highly expressed in NSCLC cells relative to normal lung cells. Functionally, TTYH3 knockdown restrained NSCLC migration, invasion, EMT, and metastasis. Mechanistic experiments demonstrated that LUCAT1 bound to ALYREF. After LUCAT1 knockdown, TTYH3 expression and mRNA stability were reduced, which was reversed by ALYREF overexpression. Furthermore, ALYREF overexpression counteracted the inhibitory effects of LUCAT1 knockdown on NSCLC cell migration, invasion, and EMT. TTYH3 overexpression eliminated the suppressive functions of ALYREF downregulation in NSCLC progression. LUCAT1 promotes TTYH3 expression via interacting with ALYREF, thereby facilitating NSCLC migration, invasion, and EMT.